The Influence of Principal Situational Leadership and Teacher Independent Training on the Pedagogical Competence of Mathematics and Natural Sciences Teachers at State Senior High Schools in Pasaman Regency - Hayati, Redhatul; Imamora, Marjoni; Demina, Demina; Haviz, M.; Yenti, Isra Nurmai (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2025)
Teachers' pedagogical competence is an essential factor in addressing the challenges of 21st-century education, particularly in the era of the Merdeka Curriculum, which requires teachers to assume adaptive and professional roles. This study aims to examine: (1) the Influence of principals' situational leadership on the pedagogical competence of science teachers at public senior high schools in Pasaman Regency; (2) the effect of teacher independent training on the pedagogical competence of science teachers; and (3) the simultaneous effect of principals' situational leadership and Teacher Independent Training on the pedagogical competence of science teachers at public senior high schools in Pasaman Regency. This study employs a quantitative ex post facto design, using questionnaires on principals' situational leadership, Teacher Independent Training, and pedagogical competence for data collection. These questionnaires were completed by 89 respondents, who served as the sample for this study. The population consisted of 115 science teachers at public senior high schools in Pasaman Regency. The results indicate a significant effect of principals' situational leadership on teachers' pedagogical competence, with a p-value of less than 0.05 in the partial t-test. The second finding confirms the effect of Teacher Independent Training on pedagogical competence, also with a significance value less than 0.05 in the partial t-test. The final finding shows a significant simultaneous effect of principals' situational leadership and Teacher Independent Training on the pedagogical competence of science teachers at public senior high schools in Pasaman Regency, based on the F-test with a p-value of less than 0.05. These findings highlight the principal’s role in applying adaptive leadership styles and emphasize the significance of self-directed training for teachers’ professional development. This research advocates for optimizing self-directed training and implementing responsive leadership to sustainably enhance teachers' pedagogical competence.